KAJIAN PRAKTIS PENILAIAN BENDA CAGAR BUDAYA LOGAM (DALAM PENENTUAN IMBALAN JASA) - Edi Triharyantoro (Balai Arkeologi Yogyakarta, 2010)
Value assesment of metal artifacts for compensation is problematic in heritage management. In Indonesia, there is no guideline to value a metal artifact and archaeological offices use different standard to determine the value metal artifacts. This has been seen as unjust among the society. In this paper, three essential aspects are proposed to be used in interpreting and identifying metal artifacts for compensation: context, rarity, and age. These three aspects are “inner considerations”. Along side with those aspects, we need to also consider other two “outer considerations”, i.e. present standard price for metal and collector's price. Combining those inner and outer considerations will help greatly to determine the value of metal artifacts for compensation.